Trends in velocity and policy expectations - David B. Gordon; Eric M. Leeper; Tao Zha (Federal Reserve Bank of Atlanta, 1997)
U.S. velocity of base money exhibits three distinct trends since 1950. After rising steadily for thirty years, it flattens out in the 1980s and falls substantially in the 1990s. This paper explores whether the observed secular movements in velocity can be accounted for exclusively by endogenous responses to changing expectations about monetary and fiscal policy. We use a model with two key features: a substitute for money in transactions and an array of assets that includes money, nominal bonds, and physical capital. The model maps policy expectations into portfolio decisions, making equilibrium velocity a function of expected future money growth, tax rates, and government spending. When expectations are estimated using Bayesian updating, simulated velocity matches the trends in actual velocity surprisingly well.
Keywords: 330; Macroeconomics; Money supply; Monetary policy; Velocity of money